Perancangan dan Pengembangan Aplikasi Android Berbasis Augmented Reality pada Mahasvin Farm menggunakan Metode MDLC - Heycal Adya Bramantyo; Ika Asti Astuti (Jurnal Teknologi Informasi dan Multimedia, 2025)
Educational tourism plays an important role in preserving nature and supporting the creative economy of local communities. Agritourism, as a subset of educational tourism, combines rec-reation with learning experiences about conservation and sustainability. Mahasvin Farm, an agro-tourism destination in Yogyakarta, incorporates this concept by showcasing rare animals such as ostriches, peacocks, ornamental chickens, and turtles. However, current methods of de-livering information, such as static boards and limited tour guides, are less effective in engaging younger audiences who prefer interactive digital media. This study aims to develop an An-droid-based application leveraging Augmented Reality (AR) technology to deliver educational content interactively. The Multimedia Development Life Cycle (MDLC) methodology was applied, consisting of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. MDLC was selected for its structured framework and capability to integrate multimedia elements, including 3D visualization, audio, and text. Blackbox testing results indicated a 100% success rate across 13 test scenarios, including menu navigation, AR marker scanning, and audio description functionality. The application successfully enhances the educational experience by providing engaging and immersive features, while also having the potential to improve digital promotion efforts for Mahasvin Farm. In conclusion, the AR-based application offers an innovative solution to improve information dissemination at Mahasvin Farm. Furthermore, it demonstrates the poten-tial for broader adoption in the technology-based agritourism sector.